Lipid mediators in immune regulation and resolution. (1st March 2019) - Gilroy, Derek W.; Bishop‐Bailey, David
Abstract : We are all too familiar with the events that follow a bee sting—heat, redness, swelling, and pain. These are Celsus' four cardinal signs of inflammation that are driven by very well‐defined signals and hormones. In fact, targeting the factors that drive this onset phase is the basis upon which most current anti‐inflammatory therapies were developed. We are also very well aware that within a few hours, these cardinal signs normally disappear. In other words, inflammation resolves. When it does not, inflammation persists, resulting in damaging chronic conditions. While inflammatory onset is actively driven, so also is its resolution—years of research have identified novel internal counter‐regulatory signals that work together to switch off inflammation. Among these signals, lipids are potent signalling molecules that regulate an array of immune responses including vascular hyper reactivity and pain, as well as leukocyte trafficking and clearance, so‐called resolution. Here, we collate bioactive lipid research to date and summarize the major pathways involved in their biosynthesis and their role in inflammation, as well as resolution. Linked Articles: This article is part of a themed section on Eicosanoids 35 years from the 1982 Nobel: where are we now? To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v176.8/issuetoc